Wielkomiejskie życie Drugiej Rzeczpospolitej w polskim filmie fabularnym okresu międzywojennego. Wstęp do tematu - Otto, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Big city life in the Second Commonwealth of Poland in Polish interwar feature films. An Introduction Polish feature films from the interwar period are to a great extent a reflection of the reality of that time. This can be seen mainly in the presentation of particular architectural objects and fashion from that time. The films are also a source of knowledge about the problems of the time: the impoverishment of the society, economic crisis, prostitution, etc. These pictures reflect reality, yet they are subject to numerous transformations, as the result of the conventions of the chosen genre.